Vilnius Cinematic Spaces: Eitvydas Doškus’ Dialogue with Almantas Grikevičius in Once Upon a Vilnius - Bidlauskienė, Gintarė (Semiotika, 2024)
This article compares two works of poetic documentary that depict Vilnius: Almantas Grikevičius’ Time Passes Through the City (1966) and Eitvydas Doškus’ Once Upon A Vilnius (2022). Employing a geocritical approach, the analysis investigates the interplay between the city and its cinematic representations. It highlights the thematic and aesthetic dialogue between the two films, contrasting Grikevičius’ modernist vision of Vilnius as a convergence of history and modernity with Doškus’ portrayal of a city in constant evolution, blending local heritage with global influences. The article aims to reveal the historically shifting strategies of Vilnius’ representation and to analyse the city’s resulting imagery and its impact. It argues that both films not only document transformations in Vilnius but also craft a distinctive perception of the city as a dynamic, intertextual, and intermedial space.